Antibacterial activity and cytotoxicity potential of propolis against selected oral pathogens using in-vitro method - Nishitha, Danda; N.Manivannan, N.Manivannan (Journal of Neonatal Surgery, 2024)
Background: Propolis is a natural resinous substance produced by honeybees and is known for its antimicrobial and therapeutic properties. It has gained attention in oral healthcare due to its ability to inhibit the growth of pathogenic microorganisms associated with dental infections. Aim: The present study aimed to evaluate the antibacterial activity and cytotoxicity potential of propolis against selected oral pathogens using an in-vitro approach. Materials and methods: Propolis extract was prepared using ethanol extraction and subjected to antibacterial analysis against Streptococcus mutans and Escherichia coli. The antibacterial activity was assessed using the agar well diffusion method at different concentrations of the extract. Cytotoxicity evaluation was performed using zebrafish embryo assay to determine cell viability and toxicological effects. The zones of inhibition and percentage of viability were recorded and analyzed. Results: Propolis extract demonstrated effective antibacterial activity against Streptococcus mutans and Escherichia coli, with greater inhibition observed against S. mutans. The antimicrobial effect increased with higher extract concentrations. Cytotoxicity analysis using zebrafish embryos showed a concentration-dependent decrease in viability. However, lower concentrations exhibited comparatively better biocompatibility, indicating reduced toxic effects within the tested range. Conclusion: The findings of the study demonstrated that propolis exhibited notable antibacterial activity against the tested oral pathogens. Increased concentrations of the extract showed enhanced inhibitory effects on microbial growth. The cytotoxicity assay revealed acceptable biocompatibility at lower concentrations, indicating its relative safety. Therefore, propolis may serve as a promising natural therapeutic agent for oral healthcare applications